Dietary Habits and Musculoskeletal Pain in Statin and Red Yeast Rice Users: A Pilot Study - Anna Raguzzini; Elisabetta Toti; Maura Palmery; Mohamed M. Abdel-Daim; Ilaria Peluso (MDPI AG, 2021)
(1) Background: Diet and statins are commonly used to treat high cholesterol (CHOL) levels. (2) Aim: To compare adherence to Mediterranean diet (Med-D), orthorexia nervosa (ON), and musculoskeletal pain in individuals in treatment with statins metabolized by CYP3A4, not metabolized by CYP3A4 or red yeast rice (RYR, containing monacolin K: MON-K). (3) Methods: starting from 80 individuals, after the exclusion of those with other causes of possible pain, 56 individuals were selected and divided into three groups according to the type of statin (CYP3A4, NO-CYP3A4 and MON-K). Adherence to the Med-D was evaluated with the MEDScore and a sub-score was calculated for fruit and vegetables consumption (MEDScore-FV). ON and musculoskeletal pain were assessed with the ORTO-15 and with the Nordic Musculoskeletal questionnaires, respectively. A retrospective analysis of CHOL decrease after treatment was conducted. (4) Results: CHOL levels were lower in CYP3A4 and NO-CYP3A4 after treatment (182.4 ± 6.3 and 177.0 ± 7.8 mg/dL, respectively), compared with MON-K (204.2 ± 7.1 mg/dL, p < 0.05). MON-K and CYP3A4 groups had a high prevalence of reported knee pain (33.3% and 18.8%, respectively) than NO-CYP3A4 group (0%, p < 0.05). A high percentage of individuals in MON-K take supplements and nutraceuticals (87.5%), whereas MEDScore-FV was higher in CYP3A4 (9.4 ± 0.2) compared to NO-CYP3A4 (7.6 ± 0.5, p < 0.05). (5) Conclusions: This study suggests that individuals receiving treatment with statins and RYR should be monitored from the perspective of plant foods' consumption and nutraceutical use, to prevent musculoskeletal pain.